Recurrent ischaemic cerebrovascular events as presenting manifestations of myeloproliferative neoplasms. (8th February 2019) - Stefanou, M. I.; Richter, H.; Härtig, F.; Wang, Y.; Örgel, A.; Bender, B.; Mengel, A.; Ziemann, U.; Poli, S.
Abstract : Background and purpose: Myeloproliferative neoplasms (MPNs) – polycythemia vera, essential thrombocythemia and primary myelofibrosis – are associated with increased risk for ischaemic cerebrovascular events (ICVEs). Due to their low prevalence, MPNs often remain undiagnosed as the cause of ICVEs. Methods: Case records at the University of Tübingen between 2014 and 2017 were screened to identify patients with MPN‐related ICVEs. Clinical features, brain imaging, laboratory findings, applied treatments and neurological outcomes were assessed. Results: In all, 3318 patients with ICVEs were identified, and amongst them 17 patients with MPN‐related ICVEs were included in a retrospective study. In 58% of these patients, ICVEs were the first manifestation of the underlying MPN; 24% presented with transient ischaemic attack and 76% with ischaemic stroke. Potentially concurrent ICVE etiologies were noted in 70% of the patients. The majority (94%) of patients were positive for the JAK2 V617F mutation, whilst in 29% recurrent ICVEs (range two to three) were noted prior to MPN diagnosis. Early MPN diagnosis and management was the only significant prognostic factor for ICVE recurrence ( P < 0.001). Discussion: Evidence is provided that, although rare, MPNs represent an underdiagnosed cause of recurrent ICVEs. High clinical awareness is warranted to identify an underlying MPN in patients presenting with sustained, abnormal blood count findings. Clinical algorithms for prompt MPN diagnosis and initiation of MPN treatment (e.g. cytoreductive therapy, phlebotomy) are required. As MPN management comprises a significant protective factor against ICVE recurrence, induction of MPN treatment should be regarded as an integral component of secondary stroke prevention in MPN‐associated ICVEs.